Czasowy całkowity zakaz reklamy otwartego funduszu emerytalnego - Jakubowski, Sebastian (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The paper discusses the effects of temporary total prohibition of Open-end Pension Fund advertising. This prohibitive regulation was in force in the years 2014–2015 and has raised many controversies, and ultimately became the subject of the Constitutional Court summons. The main thesis of the article is that temporary total prohibition of Open-end Pension Fund advertising has contributed to a decrease in the amount of contributions paid to Open-end Pension Funds and started the process of gradual and informal phasing-out of funded part of pension system in Poland. The scientific method used in this paper is economic analysis of law
Keywords: emerytury; ubezpieczenia społeczne; prawo pracy; fundusz emerytalny; otwarte fundusze emerytalne